2006
DOI: 10.1152/ajpheart.00815.2005
|View full text |Cite
|
Sign up to set email alerts
|

Dilatory responses to estrogenic compounds in small femoral arteries of male and female estrogen receptor-β knockout mice

Abstract: The objectives of this study were to determine whether acute dilatory responses to estrogen receptor agonists are altered in isolated arteries from estrogen receptor beta-deficient mice (beta-ERKO) and to gain insight into the role of nitric oxide (NO) in these responses. Femoral arteries (approximately 250 microm) from male and female beta-ERKO mice and wild-type (WT) littermates (26 female, 13 in each group; and 24 male, 12 in each group) were mounted on a Multi-Myograph. Concentration-response curves to 17b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 60 publications
2
18
1
Order By: Relevance
“…The rapid onset of the ER-␣-and ER-␤-mediated decrease in PA vasoconstriction (Ͻ20 min for PE-induced vasoconstriction and Ͻ45 min for HPV) is suggestive of a nongenomic increase in NO release. The concentrations required to mediate these effects were similar to those reported by other investigators demonstrating vasorelaxation in isolated systemic arteries (6,36). Nongenomic signaling by estrogens appear to be particularly important in "nontraditional" sex hormone target tissues (12).…”
Section: Discussionsupporting
confidence: 85%
“…The rapid onset of the ER-␣-and ER-␤-mediated decrease in PA vasoconstriction (Ͻ20 min for PE-induced vasoconstriction and Ͻ45 min for HPV) is suggestive of a nongenomic increase in NO release. The concentrations required to mediate these effects were similar to those reported by other investigators demonstrating vasorelaxation in isolated systemic arteries (6,36). Nongenomic signaling by estrogens appear to be particularly important in "nontraditional" sex hormone target tissues (12).…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, controversy exists as to whether resveratrol acts predominantly through ER␤ (27) or has mixed agonist/antagonist actions on both receptors, depending on the cell type or vascular bed studied (10). Thus, from our data and previous reports, it could be suggested that occupancy of either receptor subtypes evokes vasodilatation and that ligands with higher selectivity for one ER subtype achieve a greater biological response than those with similar affinity for both (16,35).…”
Section: Discussionmentioning
confidence: 60%
“…Each artery was mounted as an isometric preparation on stainless steel wires (diameter, 40 m) attached to a force transducer and a micrometer, respectively, as described previously (16,34). Commercially available software was used for calibrations and for data collection (Myodac, version 2.1, Danish Myo Technology).…”
Section: Patients Populationmentioning
confidence: 99%
“…Three subtypes of the ER have been identified: ER-␣, ER-␤, and GPR30 (3,7,29,39,43). Some studies have shown that the ERs have different patterns of expression and different effects at different ages (12,14).…”
Section: Discussionmentioning
confidence: 99%